Climate change effects on agriculture and food security in Tajikistan - Khakimov, Parviz; Aliev, Jovidon; Thomas, Timothy S.; Ilyasov, Jarilkasin; Dunston, Shahnila (University of Westminster Press, 2020)
Climate change is one of the main challenges for Tajikistan’s agricultural development and food security both in the medium and longer term. It is considered one of the key obstacles to achieving the country’s strategic objectives as defined in the National Development Strategy for 2016–2030, which includes ensuring food security and access to quality nutrition by 2030. Using IFPRI’s International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT), this article examines the effects of climate change on agriculture and food security in Tajikistan. The model simulation results show that yields of some major crops will decline significantly and project an overall negative effect of climate change on the agriculture sector in the country. Climate change will be one of the main challenges for food security, leading to an increased number of people at risk of hunger, malnourishment, especially among children and other vulnerable groups, and insufficient per capita calorie intake. Lower food availability may lead to higher food prices, which would negatively affect the livelihood of the population.